The Effect of the Student Teams Achievement Division Learning Model on Elementary School Students' Critical Thinking Skills in Social Studies - Ester Julia Hendriksz; Samuel Patra Ritiauw; Nathalia Yohana Johannes (Actual Insight, 2026)
Critical thinking is one of the key competencies required in 21st-century education, particularly in Social Studies learning, which aims to develop students’ analytical, evaluative, and problem-solving abilities. However, many elementary school students still demonstrate low levels of critical thinking due to the predominance of conventional teacher-centered learning approaches. This study aimed to examine the effect of the Student Teams-Achievement Divisions (STAD) learning model on the critical thinking skills of fifth-grade students in Social Studies learning at SDN 1 Amahusu. The study employed a quantitative approach using a quasi-experimental design involving 46 students, consisting of 23 students in the experimental group and 23 students in the control group. Data were collected through observation and essay-based test instruments that had undergone validity and reliability testing. Data analysis was conducted using SPSS version 25 and included descriptive statistics, validity testing, reliability testing, normality testing, homogeneity testing, paired-samples t-test analysis, and N-Gain analysis. The findings revealed that the STAD learning model significantly improved students’ critical thinking skills. The experimental group achieved a mean post-test score of 91.5, compared with 48.2 in the control group. The paired-samples t-test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant effect of the intervention. Furthermore, the average N-Gain score of 0.8440 was categorized as high. These findings indicate that the STAD learning model is an effective instructional strategy for enhancing elementary school students’ critical thinking skills in Social Studies learning through collaborative and student-centered learning activities.